Evaluating the Impact of A Nurse-Led Sexual Violence Prevention and Health Promotion Intervention: A Quasi-Experimental Study in Northern Myanmar Camps (International Journal of Nursing Education, 2025)
Objective: To evaluate the impact of a nurse-led sexual violence prevention and health promotion intervention on improving the knowledge, attitudes towards sexual violence, and awareness of help-seeking services among internally displaced people living in northern Myanmar camps.Background: Sexual violence is a widespread violation of human rights, especially affecting internally displaced persons, who are more vulnerable in such situations. Nurses are an important frontier in service delivery, and nurse-led interventions in their daily routine, such as health education, promotion, counselling, and treatment, are essential in preventing violence.Methods: A quasi-experimental study, pre-posttest design, with 154 men and women aged 18 to 49 from two camps in Kachin State, Myanmar. Participants were enrolled into two groups: intervention and control. The intervention group received nurse-led intervention integrated into their routine health promotion activities. Paired t-tests were analysed tofind within-group changes, and independent t-testswere used to assess between-group differences.Results: The intervention group showed improvement from pre-intervention to post-intervention compared to thecontrol group, knowledge (mean difference = 3.16, p < 0.001), attitudes toward sexual violence (mean difference = 1.72,p < 0.001), and help-seeking knowledge and service awareness (mean difference = 17.00, p < 0.001). Between-group analysis found no significant differences at baseline. However, post-intervention scores of the intervention group were higher than the control group for knowledge (p = 0.023), attitudes (p < 0.001), and help-seeking service awareness (p < 0.001), confirming the effectiveness of the intervention.Conclusion: The findings suggest nurse-led interventions significantly improve knowledge, attitudes, and help-seeking service awareness related to sexual violence among conflict-affected settings. The nurse-led study highlights the necessity of policy support, integration into routine health services, and more research to improve long-term and sustainability in various humanitarian settings.
Keywords: nurse-led, sexual violence, internally displaced people, conflict, Myanmar.